How do tsetse recognise their hosts? The role of shape in the responses of tsetse (Glossina fuscipes and G. palpalis) to artificial hosts. - Inaki Tirados; Johan Esterhuizen; Jean Baptiste Rayaisse; Abdoulaye Diarrassouba; Dramane Kaba; Serge Mpiana; Glyn A Vale; Philippe Solano; Michael J Lehane; Stephen J Torr (PLoS Neglected Tropical Diseases, 2011)
Palpalis-group tsetse, particularly the subspecies of Glossina palpalis and G. fuscipes, are the most important transmitters of human African trypanomiasis (HAT), transmitting >95% of cases. Traps and insecticide-treated targets are used to control tsetse but more cost-effective baits might be developed through a better understanding of the fly's host-seeking behaviour. Electrocuting grids were used to assess the numbers of G. palpalis palpalis and G. fuscipes quanzensis attracted to and landing on square or oblong targets of black cloth varying in size from 0.01 m(2) to 1.0 m(2). For both species, increasing the size of a square target from 0.01 m(2) (dimensions=0.1 × 0.1 m) to 1.0 m(2) (1.0 × 1.0 m) increased the catch ~4x however the numbers of tsetse killed per unit area of target declined with target size suggesting that the most cost efficient targets are not the largest. For G. f. quanzensis, horizontal oblongs, (1 m wide × 0.5 m high) caught ~1.8x more tsetse than vertical ones (0.5 m wide × 1.0 m high) but the opposite applied for G. p. palpalis. Shape preference was consistent over the range of target sizes. For G. p. palpalis square targets caught as many tsetse as the oblong; while the evidence is less strong the same appears to apply to G. f. quanzensis. The results suggest that targets used to control G. p. palpalis and G. f. quanzensis should be square, and that the most cost-effective designs, as judged by the numbers of tsetse caught per area of target, are likely to be in the region of 0.25 × 0.25 m(2). The preference of G. p. palpalis for vertical oblongs is unique amongst tsetse species, and it is suggested that this response might be related to its anthropophagic behaviour and hence importance as a vector of HAT.